(-5)-(-8)=g+7

Simple and best practice solution for (-5)-(-8)=g+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-5)-(-8)=g+7 equation:


Simplifying
(-5) + -1(-8) = g + 7
-5 + -1(-8) = g + 7

Multiply -1 * -8
-5 + 8 = g + 7

Combine like terms: -5 + 8 = 3
3 = g + 7

Reorder the terms:
3 = 7 + g

Solving
3 = 7 + g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-1g' to each side of the equation.
3 + -1g = 7 + g + -1g

Combine like terms: g + -1g = 0
3 + -1g = 7 + 0
3 + -1g = 7

Add '-3' to each side of the equation.
3 + -3 + -1g = 7 + -3

Combine like terms: 3 + -3 = 0
0 + -1g = 7 + -3
-1g = 7 + -3

Combine like terms: 7 + -3 = 4
-1g = 4

Divide each side by '-1'.
g = -4

Simplifying
g = -4

See similar equations:

| 4x+4=19-x | | (-37)=c+(-14) | | 6a-2-4a=3a+4+5a | | 0=-5n-2n-2n | | (-5)=b+(-11) | | -8x^2-8x+160=0 | | A-5=(-8) | | 3x*26= | | 6(x-1)+2=6x-2 | | -7y=-10-8y | | 0=-4.9t^2+.686t | | J+(-3)=4 | | 7j+4=5j | | -5x-15=-20 | | 9y=9+10y | | -12+8+5=36 | | 2x+34x^2-322=0 | | 3+(-7)=f-3 | | 3y+9-8y+6-6=-5y-12 | | -12+3x=-6 | | 9n=-117 | | 3x+9-8x+6-6=-5x-12 | | 3+(-7)=4 | | -0.9+z=0.075 | | 69=3u | | 0.06x+0.02(7-x)= | | 6p+4= | | 8-3=3x-2-8x | | 4+e=8+(-2) | | 3(5x+3)=6x-3+5x+3 | | 10b+50=30 | | 10x^2+13x+-9=0 |

Equations solver categories